Pemanfaatan Packages Pada R Programming Untuk Crawling Data Pada Social Media - Sussolaikah, Kelik (Forum Kerjasama Pendidikan Tinggi, 2021)
Social media is one of the many sources of data that can be extracted to obtain various information. In R Programming, there are thousands of packages that can be used to crawl social media data, both the default packages and the developer versions. Difficulty in extracting data will result in less than optimal research, so there is a need for adequate tools to support research. R Programming is able to become a bridge for researchers to explore existing tools, both by utilizing packages and building simple algorithms in R programming. Twitter data crawling is done through an API connection on Twitter with R Programming, so that we can get data by entering keywords according to the desired search both in realtime and at certain times as needed. With these packages it makes it easy to research in crawling social media data such as Twitter and other social media